Surgical approach to medullary thyroid carcinoma associated with multiple endocrine neoplasia type 2 - Marcos R. Tavares; Sérgio P. A. Toledo; Fábio L. M. Montenegro; Raquel A. Moyses; Rodrigo A. Toledo; Tomoko Sekyia; Claudio R. Cernea; Lenine G. Brandão (Clinics, 2012)
We briefly review the surgical approaches to medullary thyroid carcinoma associated with multiple endocrine neoplasia type 2 (medullary thyroid carcinoma/multiple endocrine neoplasia type 2). The recommended surgical approaches are usually based on the age of the affected carrier/patient, tumor staging and the specific rearranged during transfection codon mutation. We have focused mainly on young children with no apparent disease who are carrying a germline rearranged during transfection mutation. Successful management of medullary thyroid carcinoma in these cases depends on early diagnosis and treatment. Total thyroidectomy should be performed before 6 months of age in infants carrying the rearranged during transfection 918 codon mutation, by the age of 3 years in rearranged during transfection 634 mutation carriers, at 5 years of age in carriers with level 3 risk rearranged during transfection mutations, and by the age of 10 years in level 4 risk rearranged during transfection mutations. Patients with thyroid tumor >5 mm detected by ultrasound, and basal calcitonin levels >40 pg/ml, frequently have cervical and upper mediastinal lymph node metastasis. In the latter patients, total thyroidectomy should be complemented by extensive lymph node dissection. Also, we briefly review our data from a large familial medullary thyroid carcinoma genealogy harboring a germline rearranged during transfection Cys620Arg mutation. All 14 screened carriers of the rearranged during transfection Cys620Arg mutation who underwent total thyroidectomy before the age of 12 years presented persistently undetectable serum levels of calcitonin (<2 pg/ml) during the follow-up period of 2-6 years. Although it is recommended that preventive total thyroidectomy in rearranged during transfection codon 620 mutation carriers is performed before the age of 5 years, in this particular family the surgical intervention performed before the age of 12 years led to an apparent biochemical cure.